Turkey's recent trade and foreign direct investment performance - Ümit İzmen; Kamil Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2009)
This paper analyzes the changes in the structure of trade as well as the developments in the capital account of Turkey since mid-1990s and discusses the possible composition of trade flows and Turkey's attractiveness for international capital inflows in the near future. Analysis of the long-term performance of Turkish exports and imports reveals that the efforts to increase exports were successful only to a certain degree. The country's large trade deficit with the rest of the world accumulates over time and frequently ends up with a crisis which automatically reduces the trade deficit by reducing the imports. Since 2001 the transformation of exports from the low-tech products to medium-tech and to a certain degree high-tech products has taken place. While this transformation helped bring the trade deficit with the EU down, it contributed to the widening of trade deficit vis-à-vis the Asian countries and oil exporters. The initiation of the EU accession talks in 2005 invigorated the expectations for a more rapid and consistent implementation of the rules and regulations that ensure a level playing field for all companies, domestic and foreign, alike. The EU accession process enabled Turkey to attract record levels of FDI inflows. Almost all of the FDI inflows over the last four years have been composed of mergers and acquisitions, and directed mostly to service sectors and the real estate. From a longer term growth perspective Turkey needs to attract greenfield investments, especially in the manufacturing industries. In order to put Turkey in international producers' networks the current investment environment should further be improved by the implementation of long-delayed microeconomic structural reforms as well as judicial and legal reforms.
Keywords: F4; F14; 330; Turkey; European Union; Foreign Trade; Current Account; Capital Account; Außenwirtschaft; Außenhandelsstruktur; Kapitalbilanz; Direktinvestition; Türkei; EU-Staaten